Production of the antimalarial drug precursor amorphadiene by microbial terpene synthase-like from the moss Sanionia uncinata - Hyeonjin Kim; Yelim Lee; Jihyeon Yu; Jong-Yoon Park; Jungeun Lee; Sang-Gyu Kim; Youbong Hyun (Planta, 2024)
Main conclusion The microbial terpene synthase-like of the moss Sanionia uncinata displays the convergent evolution of a rare plant metabolite amorpha-4,11-diene synthesis. Abstract Despite increasing demand for the exploration of biological resources, the diversity of natural compounds synthesized by organisms inhabiting various climates remains largely unexplored. This study focuses on the moss Sanionia uncinata , known as a predominant species within the polar climates of the Antarctic Peninsula, to systematically explore its metabolic profile both in-field and in controlled environments. We here report a diverse array of moss-derived terpene volatiles, including the identification of amorpha-4,11-diene, a rare sesquiterpene compound that is a precursor for antimalarial drugs. Phylogenetic reconstruction and functional validation in planta and in vitro identified a moss terpene synthase, S. uncinata microbial terpene synthase-like 2 (SuMTPSL2), which is associated with amorpha-4,11-diene production. We demonstrate that expressing SuMTPSL2 in various heterologous systems is sufficient to produce amorpha-4,11-diene. These results highlight the metabolic diversity in Antarctica, but also provide insights into the convergent evolution leading to the synthesis of a rare plant metabolite.